Pemanfaatan Teknologi Digital dalam Pemasaran Produk Perak Yanyan Silver ke Pasar Jepang (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
The silver craft center in Sukawati District, Gianyar Regency, Bali faces significant challenges related to product marketing in the digital era. A heavy reliance on offline sales through exhibitions and tourists has resulted in slim profit margins for artisans, making their economic conditions highly vulnerable to fluctuations in visitor numbers. Additionally, silver artisans face difficulties in managing digital marketing, including limitations in writing attractive product descriptions, lack of understanding of product photography, and insufficient skills in managing social media and online stores. This situation adversely affects market reach, especially for international consumers who cannot access these products directly. To address these issues, the Japanese Literature Study Program at Mahasaraswati University Denpasar collaborated with Shitennoji University, Osaka, to conduct a community service program focused on mentoring digital marketing for silver craft products targeting the Japanese market, particularly with Yanyan Silver, one of the cooperative partners. The community service activities lasted for two months, beginning with observation and situation analysis on June 14, 2025, and concluding with evaluation at the end of August 2025. The Participatory Action Research (PAR) approach enabled active participation from artisans in every stage of the activity, from problem identification, planning, implementation, to evaluation. This approach ensures that the solutions produced are tailored to local needs and context. The marketing strategy employed used an integrated marketing mix covering product, price, promotion, and distribution through digital platforms. This facilitated easier customer access in Japan and enhanced Yanyan Silver’s brand awareness. These efforts positively impacted expanding market reach, improving the economic stability of artisans, and strengthening the competitiveness of silver craft products internationally, especially in the Japanese market.